Crystal Structures of MBi2Br7 (M = Rb, Cs) – Filled Variants of AX7 Sphere Packing1. Issue 6 (11th March 2016) - Chang, Jen‐Hui; Wolff, Alexander; Ruck, Michael
Abstract: The reinvestigation of the pseudo‐binary systems M Br–BiBr3 ( M = Rb, Cs) revealed two new phases with composition M Bi2 Br7 . Both compounds are hygroscopic and show brilliant yellow color. The crystal structures were solved from X‐ray single crystal diffraction data. The isostructural compounds adopt a new structure type in the triclinic space group P 1 . The lattice parameters are a = 755.68(3) pm, b = 952.56(3) pm, c = 1044.00(4) pm, α = 76.400(2)°, β = 84.590(2)°, γ = 76.652(2)° for RbBi2 Br7 and a = 758.71(5) pm, b = 958.23(7) pm, c = 1060.24(7) pm, α = 76.194(3)°, β = 83.844(4)°, γ = 76.338(3)° for CsBi2 Br7 . The crystal structures consist of M + cations in anticuboctahedral coordination by bromide ions and bromidobismuthate(III) layers 2 ∞ [Bi2 Br7 ] – . The 2D layers comprise pairs of BiBr6 octahedra sharing a common edge. The Bi2 Br10 double octahedra are further connected by common vertices. The bismuth(III) atoms increase their mutual distance in the double octahedra by off‐centering so that the BiBr6 octahedra are distorted. The CsBi2 Br7 type can be interpreted as a common hexagonal close sphere packing of M and Br atoms, in which 1/4 of the octahedral voids are filled by Bi atoms. The structure type was systematically analyzed and compared with alternative types of common packings. The existence of a compound with the suggested composition CsBiBr4 could not be verified experimentally. Abstract :